Efektivitas Model Problem Based Learning dalam Meningkatkan Kemampuan Pemahaman Konsep Penerapan Sila Pancasila Fase A - Veronica, Helena; Nuryani, Pupun; Murron, Faisal Sadam (Lembaga Teewan Journal Solutions, 2026)
This study was conducted to determine the effectiveness of the Problem-Based Learning (PBL) model in improving elementary school students’ conceptual understanding of the application of Pancasila principles. The study was motivated by the low level of students’ conceptual understanding observed during the preliminary study. A quantitative pre-experimental method with a one-group pretest–posttest design was employed. The participants consisted of 24 second-grade students at a public elementary school in Bandung. Data were collected using fill-in-the-blank and essay tests administered before and after the implementation of the PBL model. The average pretest score was 45.83, while the average posttest score increased to 73.02, indicating a 59.33% improvement in students’ conceptual understanding. The N-Gain score was 0.49, which falls into the moderate category, demonstrating that the PBL model effectively enhanced students’ conceptual understanding of the application of Pancasila principles. These findings indicate that integrating contextual problems through the PBL model encourages active learning and supports meaningful conceptual understanding among Phase A elementary school students.